PEMBELAJARAN MENULIS TEKS ULASAN MENGGUNAKAN MODEL DISCOVERY LEARNING BERRBANTUAN MEDIA AUDIOVISUAL PADA SISWA KELAS VIII - Inda Paradila, Inda (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is motivated by the problem of learning to write which is considered difficult by grade VIII students, especially in writing text reviews, which causes students to be lazy in writing activities. Therefore, the researcher chose discovery learning model and audiovisual media as an alternative to solve this problem. This study aims to 1) describe the planning / scenario for the implementation of learning to write review texts using the discovery learning model, 2) describe the responses of teachers and students in learning review texts using the discovery learning model, 3) determine the difficulties faced by students in learning to write review texts. using discovery learning models. The method used in this research is a qualitative descriptive method. The objects used in this study were all students of class VIII D SMP Darul Falah Cihampelas. From the research results, it shows that the student's response to the learning process of writing review text on positive statements totaling 10 statements received the answer "agree" with an average percentage of 77.7%, while negative statements totaling 10 statements got the answer " agree "with an average of 22.3%. This, of course, greatly affects student learning progress. The results of the student's writing ability increased seen from the percentage results, namely 71.7% of students scored above the average. Meanwhile, 28.3% of students scored below average. This happens because students have difficulty producing text reviews on the aspects of structure, language and spelling. In addition, there are still many students who are less able to make effective sentences, good paragraphs, use punctuation and capital letters.